Emergency Medicine Reports' LLSA Exam Study Guide 2021 - Mark, Shelly (Emergency Medicine Reports' LLSA Exam Study Guide Ser., 2020)
Emergency Medicine Reports' LLSA Exam Study Guides are widely recognized as dependable, authoritative, and convenient resources for ABEM Lifelong Learning and Self-Assessment (LLSA) test prep.